Investigating the Incidence and Coping Mechanisms for Postpartum Depression in Women of Childbearing Age in Osun State - JIDDA, Kafayah Adeola; ABDULRAHEEM, Adijat Mojisola; ONI, Ebunoluwa Ayobami; OGUNSOLA, Muftau Tijani; OYEYINKA, Abraham Jide (Ilorin Journal of Education, 2024)
This study investigated the incidence and coping mechanisms of postpartum depression among women of childbearing age in Osun State. This study employed a descriptive survey research. The research population comprised all women of reproductive age in Osun State, Nigeria. A total of 200 women were selected for sampling using a simple random sampling technique. Data collection was done using a researcher designed questionnaire. The questionnaire comprised 15 items assessing the incidence and 15 items evaluating the coping techniques. Each item was organized using a four-response format. The questionnaire items were evaluated for their validity by a panel of experts, while a reliability test of test re-test method on the questionnaire yielded reliability coefficient of 0.62. Data were analyzed using the percentage to answer research question one, while research question two was addressed using the mean and standard deviation metrics. The hypotheses were evaluated using Analysis of Variance (ANOVA) and independent t-test with a significance level of 0.05. The study found that the incidence of postpartum depression among women of childbearing age in Osun State was moderate. The coping mechanisms adopted by these women included avoiding activities that could trigger depression during the postpartum period, receiving financial support from family, as well as seeking help from religious and social groups, among other strategies. Therefore, it was recommended that health care authorities devise strategies to formulate recommendations and implement measures aimed at preventing postpartum depression (PPD) in women of reproductive age.